Evolusi Tematik Asesmen Digital dalam Pendidikan (2011–2026): Analisis Bibliometrik dan Implikasinya bagi Pendidikan Agama Islam - Amri Saputra; Abdul Munip (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
The rapid development of digital technology has significantly transformed educational systems, including learning assessment practices. Digital assessment enables more flexible, efficient, and data-driven evaluation processes. Along with the increasing integration of technology in learning, research on digital assessment has grown substantially in the scientific literature. This study aims to analyze the development and thematic evolution of digital assessment research in education during the period 2011–2026 using a bibliometric analysis approach. Data were obtained from the Scopus database using the keywords digital assessment, online assessment, and e-assessment. The analysis was conducted using the Bibliometrix package through the Biblioshiny interface in R software. The results indicate a significant increase in publications and the emergence of international research collaboration networks. Keyword co-occurrence and thematic evolution analyses reveal a shift in research focus from online assessment toward more complex themes such as learning analytics, digital learning, and the use of artificial intelligence in learning evaluation. These findings highlight the growing importance of digital assessment in technology-based learning systems, including its implications for Islamic Religious Education.